2018
DOI: 10.1371/journal.pone.0208086
|View full text |Cite
|
Sign up to set email alerts
|

A new plan quality objective function for determining optimal collimator combinations in prostate cancer treatment with stereotactic body radiation therapy using CyberKnife

Abstract: Stereotactic body radiation therapy with CyberKnife for prostate cancer has long treatment times compared with conventional radiotherapy. This arises the need for designing treatment plans with short execution times. We propose an objective function for plan quality evaluation, which was used to determine an optimal combination between small and large collimators based on short treatment times and clinically acceptable dose distributions. Data from 11 prostate cancer patients were used. For each patient, 20 pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
1
5
1
Order By: Relevance
“…More collimators also obviously increased nodes, beams, EFTT, GI, and dose to normal brain and decreased the MUs and HI, although improved PTV coverage produced slightly higher PTV D min . These results are consistent with those of Varnava et al, who conjectured that 2 collimators can do the same as the 10 collimators (17).…”
Section: Discussionsupporting
confidence: 93%
“…More collimators also obviously increased nodes, beams, EFTT, GI, and dose to normal brain and decreased the MUs and HI, although improved PTV coverage produced slightly higher PTV D min . These results are consistent with those of Varnava et al, who conjectured that 2 collimators can do the same as the 10 collimators (17).…”
Section: Discussionsupporting
confidence: 93%
“…When CK is used, it generally takes 35–50 min to deliver prostate SBRT, including a 5‐min setup time. 24 , 25 However, in our study, the average BOT was only 17 min for CK. The VOLO optimizer, a new optimization algorithm for CK, can reduce the BOT more than the previous Sequential optimization algorithm.…”
Section: Discussioncontrasting
confidence: 60%
“…When CK is used, it generally takes 35–50 min to deliver prostate SBRT, including a 5‐min setup time 24,25 . However, in our study, the average BOT was only 17 min for CK.…”
Section: Discussionmentioning
confidence: 66%
“…For lung and liver SBRT, the therapeutic ratio is essential to ensure adequate coverage of moving targets while sparing the surrounding normal tissues. The amount of irradiated volume in CyberKnife treatment depends on applied motion management strategy, adopted safety margins, and beam collimator selection 4–6 . Most of the CyberKnife treatment retrospective studies have focused on improving tracking accuracy and reducing the planning target volume (PTV) margins 1,7–11 .…”
Section: Introductionmentioning
confidence: 99%
“…This collimator allows 12‐field diameters to be used without a manual exchange of collimators 16 . At our institution, in order to improve the plan quality and time efficiency, one collimator is used for small tumors in CKS treatment and two collimator combinations (small and large) are used for the large tumors in CKS treatment 4,6,17 . We previously analyzed the intrafractional dose uncertainty in the CyberKnife XLT treatment, and found that the plan robustness is better with large collimator 12 .…”
Section: Introductionmentioning
confidence: 99%